2018
DOI: 10.1590/fst.19417
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds and chemical composition of Brazilian Cerrado fruits’ wastes: pequi almonds, murici, and sweet passionfruit seeds

Abstract: Pequi, murici and sweet passionfruit are typical fruits from Brazilian Cerrado, which stand out for their sensory attributes such as color, flavor and aroma, in addition to their high nutritional value. Their seeds are by-products from the industrial processing of juices, pulps, jellies, and others, and have great exploitation potential due to their high oil content and the presence of bioactive compounds. The present work aimed to evaluate the chemical composition of pequi almonds, and of murici and sweet pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 61 publications
0
15
0
8
Order By: Relevance
“…), characteristic that is very attractive for a nourishing material once they may promote a range of health benefits to the human body, such as the assistance in the digestion and the lowering of plasmatic cholesterol (Mattos & Martins, 2000;Wu et al, 2015). Further, the content of fiber found in this study can be equated to that of passionfruit (412.4 g kg -1 ) (Araújo et al, 2018) and chia seeds (310 g kg -1 ) (Verdú et al, 2017), which are already in the food market and constantly used as source of this component by population. FNE or carbohydrate content was indirectly calculated.…”
Section: Proximate Composition and Chemical Analyzesmentioning
confidence: 69%
“…), characteristic that is very attractive for a nourishing material once they may promote a range of health benefits to the human body, such as the assistance in the digestion and the lowering of plasmatic cholesterol (Mattos & Martins, 2000;Wu et al, 2015). Further, the content of fiber found in this study can be equated to that of passionfruit (412.4 g kg -1 ) (Araújo et al, 2018) and chia seeds (310 g kg -1 ) (Verdú et al, 2017), which are already in the food market and constantly used as source of this component by population. FNE or carbohydrate content was indirectly calculated.…”
Section: Proximate Composition and Chemical Analyzesmentioning
confidence: 69%
“…The solvents used in the extraction process—ethanol (99%, boiling point of 78 °C, specific mass of 790 kg/m 3 ), isopropanol (99%, boiling point of 82 °C, specific mass of 790 kg/m 3 ), acetone (99%, boiling point of 56 °C, specific mass of 790 kg/m 3 ), and hexane (boiling point of 69 °C, specific mass of 660 kg/m 3 )—were of analytical grade from Dynamics (Diadema, Brazil). The composition of the seeds samples is presented in Table (Araújo et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The proximate composition of the pequi kernel is shown in Table 2. For pequi kernels from Caryocar coriaceum Ramos and Souza (2011) reported 2.4% ash, 48.5% lipids, 27.1% proteins and 21.9% of carbohydrates (on a dry basis), while Araújo et al (2018) reported 5.8% ash, 50.0% lipids, 33.3% protein, 5.0% fiber, and 5.7% carbohydrates. Despite the variations between the results, it can be observed that the kernel is characterized by its high lipid content, therefore being a potential raw material for obtaining edible oil.…”
Section: Physico-chemical Characterization Of Pequi Kernelmentioning
confidence: 98%
“…The kernel can be used in oil extraction, as an ingredient in flour and sweets, or as a snack in salty or sweet form (DAMIANI et al, 2013;ALVES et al, 2014). Ramos and Souza (2011) reported that pequi fruit seeds (Caryocar coriaceum) from the Maranhão and Piauí regions have an average weight of 25.9 g, and its kernels are 1.8 g. Araújo et al (2018) reported proximate composition of pequi kernels (Caryocar coriaceum) as 50.0% lipids, 5.8% ash, 33.3% protein, 5.0% fiber and 5.7% carbohydrates. Lima et al (2007) found four major components in pequi kernels (Caryocar brasiliense): lipids (51.5%), proteins (25.3%), carbohydrates (8.3%) and dietary fiber (2.2 %), with a low moisture content (8.7%) and a high mineral content represented by ashes (4.0%).…”
Section: Introductionmentioning
confidence: 99%